Chlamydia trachomatis - Pacheco Romero, José (2015)
Chlamydia is the most common bacterial sexually transmitted disease worldwide (1,2). The World Health Organization announced 90 million new cases each year worldwide, while the Center for Disease Control (CDC) in Atlanta indicates 4 million new cases each year in the US of A (1). The infection has increased in the past two decades, the highest prevalence occurring in adolescents aged 15-19 years old. Is an issue of women's health, for reproductive harm caused.